Modeling of polymer flooding using Voronoi grid - Kireev, Timur Faritovich; Bulgakova, Guzel Talgatovna; Khatmullin, Ildus Fanusovich (Computational Continuum Mechanics, 2018)
Nowadays the part of unconventional oil in the total oil reserves in Russia is more than 60% and continues to grow. Effective recovery of such oil necessitates development of enhanced oil recovery techniques such as polymer flooding. It is impossible to use this technology without carrying out numerical simulation. Structured grids are usually used for the description of the formation geometry in reservoir simulation. However, unstructured grids have a number of advantages over classical structured grids: they allow better description of reservoir heterogeneity, provide a more accurate solution of the problem near wells, and reduce the effect of grid orientation. The study investigated the model of polymer flooding with effects of adsorption and water salinity. The model takes into account five components that includes elements of the classic black oil model. These components are polymer, salt, water, dead oil and gas. The equations of the model and the problem statement are formulated. Solution of the problem by finite volume method on unstructured Voronoi grid using fully implicit scheme is obtained and verified. To compare several different grid configurations numerical simulation of polymer flooding is performed. The oil rates obtained by a hexagonal locally refined Voronoi grid are shown to be more accurate than the oil rates obtained by a locally refined rectangular grid with the same number of cells. It is also demonstrated that the Voronoi grid helps to obtain a more realistic front of the water movement by reducing the grid orientation effect.
Keywords: flow through a porous medium; black oil model; polymer flooding; Darcy law; adsorption; Voronoi grid; grid orientation effect; implicit scheme; nonlinear differential equations; finite volume method; Newton’s method